2016
DOI: 10.1007/s12282-016-0729-9
|View full text |Cite
|
Sign up to set email alerts
|

Mammographic extent of microcalcifications and oestrogen receptor expression affect preoperative breast carcinoma in situ size estimation

Abstract: Risk of over- or underestimation of DCIS size through MEM measurement depends on DCIS ER expression and MEM itself. Identifying which patients are at a significant risk of over- or underestimation could help the breast surgeon when discussing the surgical options with the patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Studies published in the last 20 years confirm the controversial nature of the alleged association of HPV with BC. There are reports which favor the impact of HPVs in BC oncogenesis (21,75,78,(80)(81)(82)84,89), while other studies have confirmed a limited or nonexistent role of HPVs in the development of BC (3,7,18,74,76,77,79,83,(85)(86)(87)(88)(90)(91)(92).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies published in the last 20 years confirm the controversial nature of the alleged association of HPV with BC. There are reports which favor the impact of HPVs in BC oncogenesis (21,75,78,(80)(81)(82)84,89), while other studies have confirmed a limited or nonexistent role of HPVs in the development of BC (3,7,18,74,76,77,79,83,(85)(86)(87)(88)(90)(91)(92).…”
Section: Discussionmentioning
confidence: 99%
“…The 23 included studies involved a total of 3,243 breast tissue samples, collected between 2004 and 2022 from nine countries worldwide (Table SIV) (3,7,18,21,(74)(75)(76)(77)(78)(79)(80)(81)(82)(83)(84)(85)(86)(87)(88)(89)(90)(91)(92). A total of six continental regions (Asia, Europe, Oceania, north Africa and South America) were represented.…”
Section: Baseline Characteristics Of the Included Studies And Assessm...mentioning
confidence: 99%
“…This method of intraoperative assessment presumes that the location of microcalcifications on radiography is an accurate surrogate for the presence of DCIS at the pathologic specimen margin. However, there is a difference between the mammographic extent of calcifications and the histologic tumor size of DCIS, with frequent underestimation of size on mammography . In addition, not all DCIS is calcified, with low‐grade lesions being less likely to contain microcalcifications .…”
Section: Introductionmentioning
confidence: 99%